IMPLEMENTASI UNDANG-UNDANG PESANTREN DALAM MENINGKATKAN KEDISIPLINAN SANTRI: TINJAUAN DARI PERSPEKTIF PENDIDIKAN AGAMA ISLAM - Sukartiningsih Sukartiningsih; Muhamad Ansori (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
This study aims to analyze the implementation of Law Number 18 of 2019 on Islamic Boarding Schools (Pesantren) in improving student discipline at Pondok Pesantren Al-Qodiri 1 Jember. Employing a descriptive qualitative approach and a case study method, the research explores the synergy between juridical and pedagogical approaches in shaping students' character. Data were collected through interviews, participatory observations, and document analysis. The findings indicate that the implementation of the Pesantren Law at Al-Qodiri is effective through habituation strategies, enforcement of internal rules, and the internalization of Islamic values in students’ daily life. Discipline is fostered not merely as obedience to rules but as a form of spiritual awareness and moral responsibility. This research offers both conceptual and practical contributions to the development of Islamic character education based on legal foundations.